2022
DOI: 10.1109/lwc.2022.3156427
|View full text |Cite
|
Sign up to set email alerts
|

Localization via Multiple Reconfigurable Intelligent Surfaces Equipped With Single Receive RF Chains

Abstract: The extra degrees of freedom resulting from the consideration of Reconfigurable Intelligent Surfaces (RISs) for smart signal propagation can be exploited for high accuracy localization and tracking. In this paper, capitalizing on a recent RIS hardware architecture incorporating a single receive Radio Frequency (RF) chain for measurement collection, we present a user localization method with multiple RISs. The proposed method includes an initial step for direction estimation at each RIS, followed by maximum lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…3) Receiving RISs: The DMA principle was also conceptualized in the parallel work [74] for enabling RISs with baseband reception capability in order to perform explicit or implicit channel estimation with minimal number of receive RF chains. In fact, [76] presented a signal direction estimation approach with a single RF chain, while [74] designed a matrixcompletion-based channel estimation technique with relatively short training requirements, requiring much fewer receive RF chains than RIS elements.…”
Section: B Operation Modesmentioning
confidence: 99%
“…3) Receiving RISs: The DMA principle was also conceptualized in the parallel work [74] for enabling RISs with baseband reception capability in order to perform explicit or implicit channel estimation with minimal number of receive RF chains. In fact, [76] presented a signal direction estimation approach with a single RF chain, while [74] designed a matrixcompletion-based channel estimation technique with relatively short training requirements, requiring much fewer receive RF chains than RIS elements.…”
Section: B Operation Modesmentioning
confidence: 99%
“…The AoDs between the BS and each RIS are also assumed known due to the known placement of the RISs and the BS position. In the context of the latter partial CSI case, we do not deal with the problem of accurately estimating the angular channel parameters, instead we assume computationally and sensingly autonomous RISs (e.g., [72], [111], [116], [119]).…”
Section: F Orchestration With Partial Csi Observabilitymentioning
confidence: 99%
“…The authors in [95] investigated the effect of a placement of three RISs on the localization and coverage, where each RIS consists of 64 elements, with dimensions of 8 × 8, and is equipped with one (1) RF chain. The results revealed that, for better localization, it is recommended to place these RISs on the same wall and at the same height.…”
Section: A Deployment Of Rismentioning
confidence: 99%